2020
DOI: 10.4047/jap.2020.12.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of different self-adhesive resin cements: Cell viability and induction of apoptosis

Abstract: PURPOSE. The effects of four different self-adhesive resin cement materials on cell viability and apoptosis after direct and indirect exposure were evaluated using different cell culture techniques. MATERIALS AND METHODS. Self-adhesive cements were applied to NIH/3T3 mouse fibroblasts by the extract test method, cell culture inserts, and dentin barrier test method. After exposure periods of 24 h and 72 h, the cytotoxicity of these self-adhesive materials was evaluated using the MTT assay (viability) and the An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
1
5
2
Order By: Relevance
“…Regarding the cement type, our findings are inconsistent with the results of a study conducted by Sismanoglu et al [21]. They assessed the cytotoxicity level of four self-adhesive cements, including Considering the relation between the time and the cytotoxicity level, we found no association between the time and cytotoxicity level after 48 h. However, some previous studies have reported the opposite; the cytotoxicity level of different cements has increased significantly after 72 h [21,22]. Therefore, one possible explanation might be that those studies have used longer periods for the extraction process.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the cement type, our findings are inconsistent with the results of a study conducted by Sismanoglu et al [21]. They assessed the cytotoxicity level of four self-adhesive cements, including Considering the relation between the time and the cytotoxicity level, we found no association between the time and cytotoxicity level after 48 h. However, some previous studies have reported the opposite; the cytotoxicity level of different cements has increased significantly after 72 h [21,22]. Therefore, one possible explanation might be that those studies have used longer periods for the extraction process.…”
Section: Discussioncontrasting
confidence: 99%
“…Three factors are associated with the cytotoxicity level of cements; first, cement acidity induces cell apoptosis by increasing the activity of caspase. Second, the time duration which cement remains acidic, and third, the amount of monomers and unreacted components in the cement [21]. Accordingly, TheraCem PH increases in the first 24 h due to the formation of calcium hydroxide, which decreases the cement acidity in the Pesqui.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, TGSCs were used to evaluate the biocompatibility and odonto/osteogenic potential of different calcium silicate-based materials via cell proliferation assay, ALP activity and odonto/osteogenic gene expression analysis using the extract test method. The extract test method is recommended by International Standard ISO 10993-5 and is often preferred in studies examining the biocompatibility of dental materials (3,10,13,14,15). Therefore, it was preferred in the current study because both the tested materials can inhibit cell growth when in direct contact with the cells and components leaching from them can result in tissue reactions (16).…”
Section: Discussionmentioning
confidence: 99%
“…These free monomers have the potential to cause pulp injury and prevent a proper tissue healing process. 26…”
Section: Discussionmentioning
confidence: 99%